Education, lifelong learning, inequality and financial access: Evidence from African countries - Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2018)
This study investigates the role of financial access in modulating the effect of education and lifelong learning on inequality in 48 African countries for the period 1996 to 2014. Lifelong learning is conceived and measured as the combined knowledge gained from primary through tertiary education while the three educational indicators are: primary school enrolment; secondary school enrolment and tertiary school enrolment. Financial development dynamics are measured with financial system deposits (liquid liabilities), financial system activity (credit) and financial system efficiency (deposits/credit). Three measures of inequality are employed notably: the Gini coefficient; the Atkinson index and the Palma ratio. The estimation strategy is based on Generalised Method of Moments. The following findings are established. First, primary school enrolment interacts with all financial channels to exert negative effects on the Gini index. Second, lifelong learning has negative net effects on the Gini index through financial deposit and efficiency channels. Third, for the most part, the other educational levels do not significantly influence inequality through financial access channels. Policy implications are discussed.
Keywords: I28; I20; I30; O16; O55; 330; Education; Lifelong Learning; Inequality; Financial development; Africa